2008
DOI: 10.1007/s12206-007-1110-x
|View full text |Cite
|
Sign up to set email alerts
|

Cutting force model considering tool edge geometry for micro end milling process

Abstract: The analysis of the cutting force in micro end milling plays an important role in characterizing the cutting process, as the tool wear and surface texture depend on the cutting forces. Because the depth of cut is larger than the tool edge radius in conventional cutting, the effect of the tool edge radius can be ignored. However, in micro cutting, this radius has an influence on the cutting mechanism. In this study, an analytical cutting force model for micro end milling is proposed for predicting the cutting f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…10 deformation and sliding mechanisms contributes to the cutting energy, especially when the tool edge radius comes to be on the order of the undeformed chip thickness [40].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…10 deformation and sliding mechanisms contributes to the cutting energy, especially when the tool edge radius comes to be on the order of the undeformed chip thickness [40].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…They demonstrated that the ploughing ratio depends on the predicted cutting force ratio Fc/Ft. Thiele and Melkote [8] and Kang et al [9] confirmed that the cutting edge geometry has a significant effect on the cutting force components. Karpat and Özel investigated the friction characteristics of tools with curvilinear edges [10].…”
Section: Introductionmentioning
confidence: 94%
“…An analytical expression for the chip thickness of micro end milling considering the tool runout was first studied by Bao and Tansel [11]. Li et al [12] proposed an instantaneous uncut chip thickness algorithm for micro milling operation by considering the combination of an exact trochoidal trajectory of the tool tip and the tool runout. Different from conventional cutting, in micro milling, the cutting tool edge radius has an important influence on the cutting mechanism; therefore, Kang et al [13] established a cutting force model considering the edge radius of micro cutting tools, in which the ploughing effect at the tool edge and the sliding on the flank face were modelled.…”
Section: Introductionmentioning
confidence: 99%